Pengaruh Promosi pada Media Sosial TikTok dan Kualitas Produk terhadap Keputusan Pembelian Konsumen Gen Z pada Produk Skincare Glad2Glow - Fardha Octavia Pratiwi Supriyadi; Elmira Siska (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
The skincare industry has seen significant growth in the importance of maintaining skin health and appearance. This study aims to examine the influence of promotions on TikTok social media and product quality on Gen Z consumers' purchasing decisions for Glad2Glow skincare products. The study employs a quantitative method using a survey technique via an online questionnaire distributed between April and June 2025 to 80 Gen Z respondents who had viewed Glad2Glow promotions on TikTok and made purchases. Data analysis was conducted using SPSS version 27 software, including data quality tests such as validity, reliability, classical assumptions, multiple linear regression, t-test, F-test, and determination coefficient. The analysis results indicate that, partially, promotions on TikTok social media do not significantly influence purchasing decisions, with a significance value of (0.354 > 0.05) and (calculated t-value 0.932 < table t-value 1.991). Conversely, Product Quality was found to have a positive and significant effect on Purchase Decisions, with a significance value of (0.01 < 0.05) and (calculated t-value 5.551 > table t-value 1.991). Simultaneously, both variables—Promotion on TikTok Social Media and Product Quality—together have a significant effect on Purchase Decisions, as indicated by F calculated 26.763 (> F table 3.12) and significance 0.01 (< 0.05).